Analisis Konsep Pembentukan Karakter dalam Kitab Matnul Ghoyah Wat Taqrib - Nilna Silvia Nur Amila; Muhammad Odik Afifin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
In the book Matnul Ghoyah wat Taqrib by Imam Abu Syuja’ Al-Isfahani, the concept of character formation is discussed in this study. This fiqh book, which is concise and easy to understand, is intended for beginners in Islamic teachings who want to get closer to Allah SWT. Character formation in this book emphasizes the importance of moral and spiritual values ​​to be used as a foundation in daily actions, both in the relationship between humans (habluminannas) and Allah (habluminallah). This study shows that, in addition to increasing justice in muamalah, the moral quality of fiqh education can increase integrity, dependability, self-control, and social responsibility. This can prevent unfair practices and increase public trust. In addition, this book emphasizes important aspects of religious character, which include living in harmony, tolerance, and obedience in worship. There are values ​​of Islamic character education such as self-awareness, sincerity, optimism, hard work, and concern for the environment. This study combines a qualitative descriptive approach with a library research approach to strengthen the analysis. It is hoped that this study will significantly advance the Islamic-based character education system in Indonesia. This will also be an important reference for educators, researchers, and practitioners of character education in the modern era.